Digital transformation and corporate resilience: Evidence from China during the COVID-19 pandemic - AiMin Yan; Hao Ma; Dandan Zhu; Julan Xie (Quantitative Finance and Economics)
To investigate the relationship between digital transformation and corporate resilience in the face of external shocks, we empirically analyzed the relationship between digital transformation and corporate resilience in the context of COVID-19 by dividing corporate resilience into two dimensions: Resistance and recovery. The data in this paper came from manufacturing companies listed in Shanghai and Shenzhen A-shares from 2017 to 2021. The empirical results showed that there was a significant inverted U-shaped relationship between digitalization and corporate resilience. After rich robustness tests, the major findings of this paper hold. Performance surpluses and external competition positively moderate the inverted U-shaped relationship between digitalization and corporate resilience. Performance deficits negatively moderate the inverted U-shaped relationship between digitalization and corporate resilience.